Peningkatan Literasi Finansial melalui Pelatihan Perencanaan Keuangan pada Siswa Sekolah Dasar - Ratih, Inayah Swasti; Zulfikri, Robby Reza (Ngarsa: Journal of Dedication Based on Local Wisdom, 2024)
The low level of financial literacy in the community has encouraged the government to create a program to increase financial literacy in the community. In order to support this government program, this community service is carried out to improve students' understanding and knowledge regarding financial literacy in elementary school students through financial planning training. This service method uses Participatory Action Research (PAR). It is a method whose process aims at learning to solve problems and fulfill the practical needs of society, as well as the production of knowledge and the process of religious social change. The results of this research show that the level of understanding of students' financial literacy still needs to be higher, as seen from the low knowledge of needs and desires, the importance of ways of saving, and the importance of ways of giving alms. The activities are carried out by students carrying out financial planning through managing pocket money at school with budget items that the researcher has determined. From the training results, students can understand financial management well, as evidenced by the results of filling out financial planning forms with the priority of needs in Islamic finance. Keywords: Financial literacy, Budget training, Financial planning Abstrak: Rendahnya literasi finansial pada masyarakat mendorong pemerintah membuat program peningkatan literasi keuangan kepada masyarakat. Guna mendukung program pemerintah tersebut, pengabdian masyarakat ini dilakukan untuk meningkatkan pemahaman dan pengetahuan siswa mengenai literasi keuangan pada siswa sekolah dasar melalui pelatihan perencanaan keuangan. Metode pengabdian ini menggunakan Participatory Action Research (PAR) yakni metode yang prosesnya bertujuan untuk pembelajaran dalam mengatasi masalah dan pemenuhan kebutuhan praktis masyarakat, serta produksi ilmu pengetahuan dan proses perubahan sosial keagamaan. Hasil penelitian ini menunjukkan bahwa tingkat pemahaman literasi keuangan siswa masih rendah dilihat dari rendahnya pemahaman kebutuhan dan keinginan, pentingnya dan cara menabung, pentingnya dan cara bersedekah. Adapun kegiatan yang dilakukan adalah siswa melakukan perencanaan keuangan melalui praktek pengelolaan uang saku di sekolah dengan pos-pos anggaran yang sudah ditetapkan oleh peneliti. Dari hasil pelatihan yang dilakukan siswa dapat memahami pengelolaan keuangan dengan baik dibuktikan dengan hasil pengisian formulir perencanaan keuangan yang sudah sesuai dengan prioritas kebutuhan dalam keuangan syariah. Kata kunci: Literasi keuangan, Pelatihan anggaran, Perencanaan keuangan